Episodic memory differences in social and non-social contexts - Karina Grunewald; Susanne Schweizer (PLoS ONE, 2026)
Humans use existing knowledge to predict and recall events. As a social species, it has been argued that humans preferentially process and recall social information. Individuals then should be better at using prior knowledge of actors’ character traits to predict and remember their behaviour in social contexts compared to predicting and remembering trait-consequence associations in non-social contexts. To test this hypothesised social episodic memory advantage, we modified a social episodic memory paradigm to include a social and non-social condition. 215 participants (18–65 years; 43% female) learnt social (people) and non-social (airports) actors’ traits, predicting and remembering their subsequent actions across various fictional events. Participants showed better memory for social compared to non-social events. However, only in non-social contexts was recall aided by prior knowledge of the actors (i.e., recall was better for events that were consistent with previously learnt information). Participants also showed a positivity bias for both social (e.g., kind actions by others) and non-social (e.g., flights running efficiently) information recall. Social memory then is preferentially processed, and social information recalled better, regardless of whether it fits with individuals’ prior knowledge or not. This may be particularly the case in situations where information about social actors is limited and all information is critical to inform whether an individual is safe to affiliate with or should be avoided. The findings also provide preliminary evidence that positive information may be preferentially recalled in these contexts. Together these findings support better memory for social over non-social information.